In vitro affinity for nicotine of soft contact lenses of different materials. Issue 4 (August 2022) - Miglio, Federica; Ponzini, Erika; Zeri, Fabrizio; Borghesi, Alessandro; Tavazzi, Silvia
Abstract: Smoking is a risk factor for the development of microbial keratitis and corneal infiltrates in contact lens (CL) wearers. It is still unknown if this risk is directly associated with the presence of nicotine in the eye and if adherence of nicotine on the CL can enhance these effects. A better understanding of the interaction between nicotine and CL materials could offer insights to explain this risk associated with smoking. The aim of this work was to compare the affinity of nicotine to different soft CL materials. CLs from FDA groups I, II, IV, and V were incubated in a 2-mM nicotine solution for 24 h and then in a 0.9% saline solution for the next 24 h. The amount of absorbed and released nicotine per CL was deduced as a function of time (t) by ultraviolet (UV) spectrophotometry and normalised to the mass of the hydrated CL. The data were described by the equation y = b –a t −1, where a and b are constants, and b represents the mass reached at the plateau after ~ 10 min of exposure. Groups IV and V displayed the highest (0.80 ± 0.09 µg) and lowest (0.27 ± 0.08 µg) nicotine absorption per mg of hydrated CL, respectively. The CL affinity for nicotine could be ascribed to the interaction between the positive charge of nicotine pyrrolidine nitrogen and the negative charges of the CLs, especially for the ionic IV group.